Influence of Age, Job Status, ICT Literacy Skills and ICT Use on Task Performance of Library Personnel in Public Universities. - Oyedipe, Wuraola Janet; Popoola, Sunday Olanrewaju (International Journal of Knowledge Content Development & Technology, 2019)
ABSTRACT The purpose of the study is to investigate the influence of demographic factors (age and job status), level of ICT skills possessed by respondents and ICT use on task performances of library personnel. The study employed descriptive survey of correlation design. The study samples were 248 library personnel made up of librarians and library officers referred to as (library professionals) in public university libraries in South-west, Nigeria. Data was collected by questionnaire. The study established significant positive correlation between age, job status, ICT skills and task performance. Also, Anova test found significant joint influence of age, job status, ICT skills and ICT use on task performances of respondents. The study further indicated that age, job status, ICT skills possessed by respondents and ICT use had relative significant influence on task performances of respondents. It is therefore recommended that, library personnel must leverage their demographics positively to bring about positive disposition to their jobs while all categories of workers must ensure they possessed the requisite ICT skills that will ginger ICT use for effective task performance. URL: http://ijkcdt.net/xml/21160/21160.pdf